Եկեղեցին որպէս բարոյական համայնք. աստուածաբանական մտորումներ - Գալստանեան, Տ․ Բագրատ Եպս․ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Предметом для своих размышлений автор статьи сделал реальность Церкви как нравственной общности. В этом вопросе он особенно акцентирует свое внимание на обрядовой жизни Церкви, особенно на таинствах Святого Крещения и Святого Причащения, стараясь также сделать очевидной нравственную роль Церкви в современном мире. The author of the article reflects on the reality of the Church as a moral community. In this matter, he focuses especially on the ritual life of the Church, especially on the sacraments of Holy Baptism and Holy Communion, and also tries to make the moral role of the Church in the modern world evident.
Keywords: Կրօնագիտութիւն